The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1557/jmr.2015.209
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the weldability, microstructure and mechanical properties of flux assisted Nd:YAG laser welds of AISI 904L

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…2,3 Fabrication of 5 mm thick SASS 904L weld plates using flux-assisted Nd: YAG laser. 4 was also reported. The selective laser melting method was also attempted by researchers for fabrication purposes.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…2,3 Fabrication of 5 mm thick SASS 904L weld plates using flux-assisted Nd: YAG laser. 4 was also reported. The selective laser melting method was also attempted by researchers for fabrication purposes.…”
Section: Introductionmentioning
confidence: 80%
“…2 AISI 904L is a premium variant of SASS grade with traces of carbon and is well known for its advantageous properties like resistance offered to corrosion, pitting crevice, and acid attacks. [3][4][5][6] By utilizing the said properties this special grade steel it can be used for applications including aerospace, marine, defense, and also in petrochemical industries. To take full advantage of the merits of AISI 904L, proper joining methods that too with optimized process parameters have to be used for autogenous joining of this special grade of steel.…”
Section: Introductionmentioning
confidence: 99%
“…9 Attributed to the above-mentioned exceptional qualities and superior properties, AISI 904L is widely utilized in aerospace applications, nuclear power plants, boilers, refineries, maritime applications, defense, construction, and chemical sectors, as well as offshore projects. 10,11,12,13,14,15 To retain the properties of AISI 904L during such challenging applications, it was equally critical to employ suitable welding techniques. Zambon et al 4 and Sathiya et al 16 used CO 2 laser while Devendranath et al 14 employed flux assisted Nd: YAG laser to weld 904L plates, but all researchers reported that the depth of weld penetration (DOP) attained was only 5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,12,13,14,15 To retain the properties of AISI 904L during such challenging applications, it was equally critical to employ suitable welding techniques. Zambon et al 4 and Sathiya et al 16 used CO 2 laser while Devendranath et al 14 employed flux assisted Nd: YAG laser to weld 904L plates, but all researchers reported that the depth of weld penetration (DOP) attained was only 5 mm. The same result was reported by Devendranath et al 17 when continuous and pulsed current gas tungsten arc welding was used to fabricate 904L joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation